Cartilage-inspired self-assembly glycopeptide hydrogels for cartilage regeneration via ROS scavenging - Zhijian Zhao; Xiaowei Xia; Junlin Liu; Mingzhuang Hou; Yang Liu; Zhangzhe Zhou; Yong Xu; Fan He; Huilin Yang; Yijian Zhang; Changshun Ruan; Xuesong Zhu (Bioactive Materials, 2024)
Cartilage injury represents a frequent dilemma in clinical practice owing to its inherently limited self-renewal capacity. Biomimetic strategy-based engineered biomaterial, capable of coordinated regulation for cellular and microenvironmental crosstalk, provides an adequate avenue to boost cartilage regeneration. The level of oxidative stress in microenvironments is verified to be vital for tissue regeneration, yet it is often overlooked in engineered biomaterials for cartilage regeneration. Herein, inspired by natural cartilage architecture, a fibril-network glycopeptide hydrogel (Nap-FFGRGD@FU), composed of marine-derived polysaccharide fucoidan (FU) and naphthalenephenylalanine-phenylalanine-glycine-arginine-glycine-aspartic peptide (Nap-FFGRGD), was presented through a simple supramolecular self-assembly approach. The Nap-FFGRGD@FU hydrogels exhibit a native cartilage-like architecture, characterized by interwoven collagen fibers and attached proteoglycans. Beyond structural simulation, fucoidan-exerted robust biological effects and Arg-Gly-Asp (RGD) sequence-provided cell attachment sites realized functional reinforcement, synergistically promoted extracellular matrix (ECM) production and reactive oxygen species (ROS) elimination, thus contributing to chondrocytes-ECM harmony. In vitro co-culture with glycopeptide hydrogels not only facilitated cartilage ECM anabolic metabolism but also scavenged ROS accumulation in chondrocytes. Mechanistically, the chondro-protective effects induced by glycopeptide hydrogels rely on the activation of endogenous antioxidant pathways associated with nuclear factor erythroid 2-related factor 2 (NRF2). In vivo implantation of glycopeptide hydrogels successfully improved the de novo cartilage generation by 1.65-fold, concomitant with coordinately restructured subchondral bone structure. Collectively, our ingeniously crafted bionic glycopeptide hydrogels simultaneously rewired chondrocytes’ function by augmenting anabolic metabolism and rebuilt ECM microenvironment via preserving redox equilibrium, holding great potential for cartilage tissue engineering.